Pengaruh Orang Tua dan Guru Bimbingan dan Konseling Terhadap Perilaku Cyberbullying - Azam Arifyadi; Mardi Lestari; Nur Eka Wahyuningsih Riyadi; Hasan Hasan (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The problem in this study is how parents and guidance and counselling teachers influence students' cyberbullying behavior, the extent to which parental influence contributes to students' cyberbullying behavior, and the impact of guidance and counselling teachers' influence on students' cyberbullying behaviour. This study aims to determine the effect of parents and guidance and counselling teachers on students' cyberbullying behavior. The type of research used in this study is causal-comparative research. This study's subjects are students' parents and guidance and counselling teachers at Palu City State Vocational School. Data collection was done through questionnaires and interviews. The research data were analyzed using multiple linear regression tests. Simultaneously, there is a significant influence between the role of parents and guidance and counselling teachers on students' cyberbullying behavior at Palu City State Vocational School.